Complex disease names. (Eurasian Journal of Philology Science and Education, 2015)
In this scientific article the morphological methods for forming names of complex diseases that relate to a person were discussed. Also it was described that in the Kazakh language names of diseases are formed by the addition of two or more words . Related to this there were given specific examples. In the Kazakh language , there are several ways to form the name of various diseases. This article describes auniform system and the structure of these names and peculiar model of word formation. In Kazakh language vocabulary as part of lexical items parts of speech such as noun + noun , adjective + adjective , noun + verb , verb + verb + pronoun pronoun , adjective + noun are used.Complicated diseases names formed in this way are considered as part of a several big lexical groups. There are the following features of the formation of words in the complex diseases' names; firstly, the names ofcomponents in interconnected by valency secondly, designation of disease names based on the meaning, semantic boundary and sound combination of words.
Keywords: morphological methods; word formation model; complex names; semantics